Human and social knowledge in the age of AI: ethics of the face and practical wisdom (Práxis Educativa, 2025)
Ethical questioning constitutes an integral part of scientific and academic cultures, as privileged places of critical intellectuality, becoming especially relevant in a world marked by the widespread use of artificial intelligence (AI) systems. To what extent does this progress serve the purposes of human development? Starting from this core inquiry, reflection on ethics in research in the Human and Social Sciences is framed here within a relational ethics grounded in values of alterity. The possibilities offered by AI tools represent a major challenge for those engaged in science, placing authors before unprecedented and extraordinarily promising work opportunities, while also running the risk of excessive trust, driven by eager but insensitive and uncritical consumers. Thus, by recognizing both the positive and negative impacts of AI and, in line with the recommendations of the United Nations Educational, Scientific and Cultural Organization – UNESCO (2024), the challenges of scientific research in the Social and Human Sciences are addressed through three fundamental axes of reflection and action: training, regulation, and research. Conceived within a logic of dynamic articulation, these three axes serve as the basis for the development of an ethical intelligence, a practical wisdom of an eminently prudential nature, here described as the ethics of the face or ethics of hospitality.Keywords: Human and social knowledge. Ethics of the face. Practical wisdom.